Contribution of EU funds to regional development in the Czech Republic: Presumption for improving the quality of life - Brigita Páleníková; Michaela Staníčková (World Economy and Policy (WEP), 2023)
Where is the best place to live? Which area in the Czech Republic has the highest quality of life? There are localities where problems are concentrated. People usually decide where to live several times in their lifetime. They want a healthy, materially fulfilling life in a cultural, socially supportive and safe environment that is professionally managed. The way forward is to live where these values are optimal or to demand improvements from the existing state and local government. To this end, it is important to implement appropriately targeted regional policies. However, effective and efficient regional policy decisions can only be made if policy makers make decisions based on sound information, i.e., in practical terms, if they have relevant data. Only under such conditions can adequate and necessary evidence-based policy-making be implemented. Data analysis and detailed comparison of territories can help policy makers better set strategic priorities to effectively address the problems inherent in a given territory and develop it. The article aims to evaluate the level of EU funds (European Structural and Investment Funds in terminology of the programming period 2014-2020) absorption in cohesion regions of the Czech Republic as a prerequisite for subsequent assessing the level of regional development and quality of life through individual indicators, or composite indices.
Keywords: 330; ESIF; composite index; quality of life; EU cohesion policy; evidence-based policy; regional development/disparities